Засада рівного виборчого права при виборах народних депутатів України - Марцеляк, С. М.; Martseliak, S. M. (Вісник Маріупольського державного університету. Сер. : Право. - 2013. - Вип. 6. - С. 253-259, 2013)
Підкреслено, що засада рівного виборчого права передбачає, що громадяни України, які мають виборчі права, мають рівні можливості щодо їх реалізації та беруть участь у виборах на рівних умовах, їм гарантуються однакові форми, способи і засоби захисту порушення суб’єктивного активного і пасивного виборчого права. Виконано аналіз теоретичних положень та ідей, норм виборчого законодавства, що стосуються сутності та змісту засади рівного виборчого права при виборах народних депутатів України, визначено її переваги і проблеми забезпечення, а також обґрунтовано пріоритетні напрямки гарантування рівності виборчих прав на парламентських виборах.

One of the basic principles of parliamentary elections in Ukraine at the level of general principles, direct and free elections is the principle of equal suffrage, which is a manifestation of the constitutional principle of equality and civil rights. This principle corresponds to the greatest extent in modern democratic nature of elections Institute, ensuring equal participation of voters in the formation of the state parliament. Reality also equal suffrage in the election of deputies of Ukraine requires a detailed legislative consolidation of the principles taking into account international practices and ensures compliance with its direct parliamentary elections. Issues relevant entity principles of equal suffrage in the election of people's deputies of Ukraine. The principle of equal suffrage states that citizens of Ukraine who have the right to vote, have equal opportunities for their realization and participate in elections on an equal footing, they are guaranteed the same forms, methods and means of protection violation subjective active and passive suffrage. The analysis of theoretical positions and ideas, norms of electoral legislation regarding the nature and content of the principle of equal suffrage in the election of people's deputies of Ukraine is made; also it was determined its advantages and problems of providing, as well as substantiated priority directions of ensure equal voting rights in parliamentary elections.

Выполнен анализ теоретических положений и идей, норм избирательного законодательства, касающиеся сущности и содержания основ равного избирательного права при выборах народных депутатов Украины, определены его преимущества и проблемы обеспечения, а также обоснованы приоритетные направления гарантирования равенства избирательных прав на парламентских выборах.
The principle of equal suffrage in the election of people's deputies of Ukraine
Keywords: засади виборів; виборці; рівне виборче право; виборчий процес; народні депутати України; principles of elections; voters; equal suffrage; electoral process; people's deputies of Ukraine; принципы выборов; избиратели; равное избирательное право; избирательный процесс; народные депутаты Украины